Problem Solving Analysis Through Tests in View Of Student Learning Achievement - Rizqi , Putri Adila Dwi; Darmayanti, Rani; Sugianto, Rahmad; Choirudin, Choirudin; Muhammad, Ilham (Indonesian Journal of Learning and Educational Studies, 2023)
This research is motivated by the importance of problem solving abilities for students. The importance of having problem solving skills is one of the main tasks in learning mathematics, moreover the process of solving mathematical problems is the essence of mathematics. The purpose of writing this paper is to find out how problem-solving abilities through test questions are assessed from student achievement. Data collection was carried out in the Lamongan area with the subjects being grade VI elementary school students who were selected based on the results of student achievement which were then grouped into 3 categories, low, medium and high. The method used is descriptive qualitative with data collection techniques carried out by administering tests. Based on the results of the field trials, it was found that the ability to solve mathematical problems using test questions for students who are classified as having high learning achievement fulfills 3-4 indicators of problem solving. Students who are classified as having moderate learning achievement fulfill 3-2 indicators of problem solving. Meanwhile, students who are classified as having low learning achievement are unable to meet the indicators of solving mathematical problems